2022
DOI: 10.1039/d1ta09347a
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a tandem S-scheme GDY/CuI/CdS-R heterostructure based on morphology-regulated graphdiyne (g-CnH2n−2) for enhanced photocatalytic hydrogen evolution

Abstract: As a new two-dimensional (2D) carbon hybrid material, graphdiyne (GDY) has attracted much attention due to its good conductivity, adjustable electronic structure and special electron transfer enhancement properties. It has...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 76 publications
1
32
0
Order By: Relevance
“…Thus, adducts of DMPO–˙OH and DMPO–˙O 2 − can be found in aqueous solution and methanol, respectively. 9,29,66 Fig. 7(g) shows the DMPO–˙OH EPR signal of the photocatalyst in the dark and after irradiation for 180 s. The EPR signal of CdS is negligible, while the signal of In 2 O 3 can be found clearly.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, adducts of DMPO–˙OH and DMPO–˙O 2 − can be found in aqueous solution and methanol, respectively. 9,29,66 Fig. 7(g) shows the DMPO–˙OH EPR signal of the photocatalyst in the dark and after irradiation for 180 s. The EPR signal of CdS is negligible, while the signal of In 2 O 3 can be found clearly.…”
Section: Resultsmentioning
confidence: 97%
“…Taking CdS as an example, the band gap energy of 2.4 eV and the appropriate conduction band position meet the thermodynamic requirements of the proton reduction reaction. 8,9 The construction of some special structures with spatial separation effects can signicantly improve the photocatalytic activity of semiconductors. 10 According to the reported literature, Lan et al found that based on the integration of the hexagonal cubic core-shell structure with the nanorod morphology, the obtained concentric CdS nanorod phase junctions exhibited high H 2 yield and good stability.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the valence band (VB) values of p-type semiconductors are 0.10 eV larger than the flat band potential tested under the calomel electrode. , That is, the VB values of CoO–3NiO and 0.10P–CONO are calculated to be 1.05 and 0.89 eV, respectively. Under the standard hydrogen electrode, the VB values of CoO–3NiO and 0.10P–CONO are calculated by E NHE = E SCE + 0.24 eV . The VB values of CoO–3NiO and 0.10P–CONO are calculated to be 1.29 and 1.13 eV.…”
Section: Resultsmentioning
confidence: 99%
“…The electrons in the CB of CeO 1.66 are rapidly combined with the holes in the VB of CoP due to Coulomb attraction, internal electric field, and energy band bending. 53,54 The remaining holes in the VB of CeO 1.66 are consumed by the sacrificial reagent (TEOA), while the electrons in the CB of CoP will participate in the reduction of H + to generate clean energy (H 2 ).…”
Section: Potential Reaction Mechanismmentioning
confidence: 99%